Detection of Leishmania (L.) infantum in stray dogs by molecular techniques with sensitive species-specific primers - Silva, Rodrigo C.; Richini-Pereira, Virgínia B.; Kikuti, Mariana; Marson, Pâmela M. [UNESP]; Langoni, Helio [UNESP] (Taylor & Francis, 2017)
Background: Canine visceral leishmaniasis (CVL) is a worldwide parasitic zoonosis caused by Leishmania (Leishmania) infantum around the world. Canids are the definitive hosts and sand flies the intermediate hosts. Objective: To test the hypothesis that a new species-specific primers (Lch14:Lch15, targeting a multiple alignment for L. infantum kDNA minicircle) is an efficient diagnostic tool for L. infantum. Methods: The presence of L. infantum DNA was assessed in blood samples of 69 stray dogs using the conventional PCR (cPCR) and quantitative PCR (qPCR). Additional 50 lymph nodes and 50 bone marrow samples (positive and negative samples for parasitological tests) from dogs from endemic and nonendemic areas for CVL were also used. Results: L. infantum strains, and all positive lymph node and bone marrow samples for parasitological test gave positive results for cPCR and qPCR, presenting analytical sensitivity of ∼10° parasite mL−1. For the blood samples, 40/69 (58%; CI 95%; 46%-69%) resulted positive for L. infantum in both tests. All positive samples were confirmed by sequencing. Conclusion: This study showed the importance of the specific detection of L. infantum based on species-specific primers by molecular techniques, highlighting the application as a confirmation method in epidemiological studies and to adopt the best control measures.
Keywords: Canine; KDNA; Leishmania infantum; PCR; Stray dogs